Lightweight enterprise architectures - Theuerkorn, Fenix (Auerbach Publications, 2004)
Based on the author's 20 years of experience in IT, Lightweight Enterprise Architectures explains an architectural approach that enables a quick alignment of technology to business strategy. The author begins by taking readers through the typical enterprise and its challenges, then presents a framework that facilitates the adoption of enterprise architecture and provides methods to implement the framework. The book presents a lightweight methodology and philosophy that is easily adopted and quickly provides value. It delineates how this approach can help readers avoid most of the pitfalls of t.